Development of encyclopedia medicinal plants in the Natuna Malay community - Sarinah Sarinah; Ari Sunandar; Hanum Mukti Rahayu (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The Malay people of the Natuna Regency still uphold the culture of utilizing medicinal plants. Medicinal plants have local potential that must be preserved. Preservation of medicinal plants can be done through local potential-based education presented in learning media. Integrating local potential presented in the encyclopedia learning media will certainly make it easier for students to understand the concept of the material they are learning. This research aims to develop a valid and practical Natuna Malay community medicinal plant encyclopedia using the 4D development model. The research instruments used were a validation questionnaire, response questionnaire, interview sheet and observation sheet. The subjects in this study were students of class X MIPA 1 and X MIPA 2 (28 students). The results show that the encyclopedia has a validity level from material experts of 98.88% (very valid), media experts of 99.52% (very valid) and language experts of 88.33% (very valid). Based on the results of the student response in the small-scale trial, the practicality level was 81.62% (positive), and the large-scale trial was 98% (very positive). This shows that the encyclopedia of medicinal plants of the Natuna Malay community is very feasible to use as a learning media for students on biodiversity material, and this encyclopedia media can also serve as a means of preserving the local wisdom of the Natuna Malay community in utilizing plants as independent medicine.Abstrak. Masyarakat Melayu Kabupaten Natuna masih menjunjung tinggi budaya memanfaatkan tanaman obat. Tumbuhan obat merupakan potensi lokal yang harus dilestarikan. Pelestarian tumbuhan obat dapat dilakukan melalui pendidikan berbasis potensi lokal yang disajikan dalam media pembelajaran. Dengan mengintegrasikan potensi lokal yang disajikan dalam media pembelajaran ensiklopedia tentunya akan memudahkan siswa dalam memahami konsep materi yang dipelajarinya. Penelitian ini bertujuan untuk mengembangkan ensiklopedia tumbuhan obat masyarakat Melayu Natuna yang valid dan praktis dengan menggunakan model pengembangan 4D. Instrumen penelitian yang digunakan adalah angket validasi, angket respon, lembar wawancara dan lembar observasi. Subjek dalam penelitian ini adalah siswa kelas X MIPA 1 dan X MIPA 2 yang berjumlah 28 siswa. Hasil penelitian menunjukkan ensiklopedia memiliki tingkat validitas dari ahli materi sebesar 98,88% (sangat valid), ahli media sebesar 99,52% (sangat valid) dan ahli bahasa sebesar 88,33% (sangat valid). Tingkat kepraktisan berdasarkan hasil respon siswa pada uji coba skala kecil sebesar 81,62% (positif) dan uji coba skala besar sebesar 98% (sangat positif). Hal ini menunjukkan bahwa ensiklopedia tanaman berkhasiat obat masyarakat Melayu Natuna sangat layak digunakan sebagai media pembelajaran peserta didik pada materi keanekaragamn hayati dan media ensiklopedia ini juga dapat berfungsi sebagai sarana pelestarian kearifan lokal masyarakat Melayu Natuna dalam memanfaatkan tumbuhan sebagai pengobatan mandiri.